1993
DOI: 10.1002/jobm.3620330310
|View full text |Cite
|
Sign up to set email alerts
|

Production of cell wall‐degrading enzymes by three isolates of Aspergillus niger under different cultivation conditions

Abstract: Three strongly pathogenic isolates of Aspergillus niger were capable of producing pectolytic, cellulolytic and proteolytic enzyme activities in various culture media, extracellularly, indicating the positive correlation between in vitro enzyme production and virulence of the pathogens.Cell wall-degrading enzymes play an important role during pathogenesis (ALBERSHEIM et al. 1969, MEHTA et al. 1974. Production of individual enzymes by the pathogens in a culture medium and the amount of activity in a crude enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Medium C which contained pectin supported maximum exo-PL suggesting the adaptive nature of the exo-PL of all the three thermophilic fungi under study. Similarly Mehta et al, (1993) have reported the adaptive nature of PL produced by Aspergillus niger.…”
Section: Resultsmentioning
confidence: 91%
“…Medium C which contained pectin supported maximum exo-PL suggesting the adaptive nature of the exo-PL of all the three thermophilic fungi under study. Similarly Mehta et al, (1993) have reported the adaptive nature of PL produced by Aspergillus niger.…”
Section: Resultsmentioning
confidence: 91%